2000
DOI: 10.4269/ajtmh.2000.62.644
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of typhoid fever in the Dong Thap Province, Mekong Delta region of Vietnam.

Abstract: Abstract. A population-based surveillance for typhoid fever was conducted in three rural communes of Dong Thap Province in southern Vietnam (population 28,329) for a 12-month-period starting on December 4, 1995. Cases of typhoid fever were detected by obtaining blood for culture from residents with fever Ն 3 days. Among 658 blood cultures, 56 (8.5%) were positive for Salmonella typhi with an overall incidence of 198 per 10 5 population per year. The peak occurrence was at the end of the dry season in March and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 18 publications
14
120
1
1
Order By: Relevance
“…Differences in study methodology as well as the epidemiology of the disease between the study sites probably account for the lower incidence observed in Jakarta than in Delhi. A study from Vietnam utilizing passive surveillance showed a culture-confirmed typhoid fever incidence similar to our findings: 3.6, 5.3, and 4.3 per thousand populations per year among those 2 to under 5 years, between 5 to 9 years, and between 10 to 19 years, respectively [22].…”
Section: Discussionsupporting
confidence: 89%
“…Differences in study methodology as well as the epidemiology of the disease between the study sites probably account for the lower incidence observed in Jakarta than in Delhi. A study from Vietnam utilizing passive surveillance showed a culture-confirmed typhoid fever incidence similar to our findings: 3.6, 5.3, and 4.3 per thousand populations per year among those 2 to under 5 years, between 5 to 9 years, and between 10 to 19 years, respectively [22].…”
Section: Discussionsupporting
confidence: 89%
“…Enteric fever is seen in all age groups and outbreaks are more common in summer season affecting mainly children [7,8]. Initiation of population-based typhoid fever incidence studies has improved the available typhoid fever incidence data [9,10]. Incidence rates of typhoid fever measured among age cohorts allows us to understand its age distribution and this can be extrapolated to the general population [10].…”
Section: Introductionmentioning
confidence: 99%
“…Community based studies have consistently shown higher levels of typhoid than public health figures suggest (Parry et al, 2002). Annual incidence rates of 198 per 100,000 in the Mekong Delta region of Vietnam (Lin et al, 2000) and 980 per 100,000 in Delhi, India (Sinha et al, 1999) have recently been reported. According to the best global estimates, there are at least 16 million new cases of typhoid fever each year, with 600,000 deaths (Ivanoff, 1995).…”
Section: Incidence Of Typhoid Fevermentioning
confidence: 99%